Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Perilaku Siswa di SMK Kesehatan Samarinda - Abdul Razak, Andi; Jannah, Fathul; Saleh, Khairul (el Buhuth: Borneo Journal of Islamic Studies, 2019)
Islamic teaching is a physical and spiritual guidance based on the holy Qur’an towards students in order to build a muslim personality completely. To have the good attitudes, students are expected to pay attention to the religion based learning as the control in the student’s life. Generally the aim of Islamic teaching is to build students who are faithful and devout to Allah SWT and have good characters. The function of Islamic teaching is to internalize faith and piety to Allah SWT and habituate students to implement the good characters both in family and school. Population in this research was all students of SMK Kesehatan Samarinda consisting of 426 students in the academic year of 2017/2018 with purposive sampling technique. Data collection techniques were questionnaires, observation and interviews. Data analysis technique used product moment formulation. The analysis shows that the two variables of the test by using Product Moment Correlation result in r calculation of 0,676 which is then interpreted by using table r, on dk=36-2=34 with confidence level of 95% or margin error of 5%, r calculation (0.632) is between 0.60 – 0.799 (strong). Based on the result of the research, it can be concluded that Islamic teaching has a strong or positive influence towards the student’s attitudes at SMK Kesehatan Samarinda.